Lung Ultrasound Practice in Australian and New Zealand Neonatal Intensive Care Units—A Survey - V. Gruber; S. Morakeas; B. Schwaberger; M. B. Tracy (Journal of Paediatrics and Child Health, 2026)
ABSTRACT Introduction Lung ultrasound (LUS) is increasingly used in neonatal intensive care units (NICUs) as a bedside, radiation‐free imaging tool for assessing respiratory conditions. Despite its advantages, data on current LUS practices in Australasian NICUs are limited. This study aimed to evaluate LUS use across NICUs in both countries. Methods A structured, anonymous survey was distributed via REDCap to NICU heads of departments in Australia ( n = 29) and New Zealand ( n = 6). The 45‐item questionnaire examined LUS frequency, indications, clinical and research use, staff training, equipment and perceived barriers. It was based on previous surveys and refined through expert feedback. Data were collected anonymously between October 2024 and July 2025. Results Twenty‐nine NICUs participated (82.9% response rate). Routine use of LUS was reported by 10.3% of units, occasional use by 65.6% and non‐use by 24.1%. LUS was used primarily for clinical purposes in 65.5% of units, for both clinical and research purposes in 17.2%, and for neither in 17.2%. Common indications included pleural effusion (79.3%), pneumothorax (75.9%), respiratory distress syndrome (58.6%), pneumonia (51.7%), transient tachypnoea of the newborn (48.3%) and atelectasis (37.9%). LUS was considered the first‐line imaging modality for pneumothorax in 79.3% of units. In 75.9% of units, at least one senior consultant had received training in LUS, and in 55.2%, fellows were trained and encouraged to perform LUS. Inconsistent use was not attributed to limited access to ultrasound equipment. Conclusion Routine LUS use across Australasian NICUs remains limited. Broader adoption may be supported through targeted training, institutional protocols and quality management frameworks.